Tunable capacitor-varistor response of CaCu3Ti4O12/CaTiO3 ceramic composites with SnO2 addition - Cotrim, G. [UNESP]; Cortés, J. A. [UNESP]; Moreno, H. [UNESP]; Freitas, S. M.; Rezende, M. V.S.; Hein, L. R.O. [UNESP]; Ramírez, M. A. [UNESP] (Elsevier, 2020)
CaCu3Ti4O12/CaTiO3 (CCTO/CTO) composites with additions of x% SnO2 (x = 0, 1, 2, and 5%) were prepared using the low cost, nontoxic, and simple solid-state reaction. The high dielectric loss associated with CCTO-based ceramics limits applications and drives the development of new solutions (e.g., ceramic composites). The incorporation of the Sn4+ ions in the CCTO structure predicted using atomistic simulations was confirmed experimentally by the Rietveld analysis and scanning electron microscopy (SEM), and its influence on the dielectric and nonohmic response was evaluated using impedance spectroscopy and current-voltage measurements. The results show that the doubly-ionized oxygen vacancies (VO••) generate enhanced grain boundary response, optimizing the dielectric permittivity at 1 kHz for samples with x = 2% (ε⁓1.42 × 105). On the other hand, the nonlinear coefficient was enhanced on the sample with x = 1% (α⁓7.0) with low leakage current (0.534 mA) and improved breakdown electric field (Eb⁓1.274 kV/cm). Thus, our work demonstrates the possibility to tune the dielectric, and nonohmic response using CCTO/CTO/SnO2 composites based on the internal barrier layer capacitor effect.
Keywords: Atomistic modeling; CaCu3Ti4O12/CaTiO3 composites; Dielectric; Nonohmic